2016
DOI: 10.1038/srep22857
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of All-Arthroscopic Versus Mini-Open Repair of Rotator Cuff Tears: A Meta-Analysis

Abstract: The objective of this study was to compare outcomes in patients with rotator cuff tears undergoing all-arthroscopic versus mini-open rotator cuff repair. A systematic review and meta-analysis of outcomes of all-arthroscopic repair versus mini-open repair in patients with rotator cuff repair was conducted. Studies meeting the inclusion criteria were screened and included from systematic literature search for electronic databases including Medline, Embase, Cochrane CENTRAL, and CINAHL library was conducted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 25 publications
0
29
0
5
Order By: Relevance
“…The percentage of patients with failure after tendon to bone repair is relatively high. [34][35][36] The insertion of tendon/ ligament and bone is a strong mechanical structure established via a collagen fiber architecture and mineral composition in the native enthesis. 5,37-39 Therefore, it is likely that a fibrous membrane system that generates a fiber architecture and mineral composition will increase the feasibility of tendon to bone healing and may be the key to improve clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of patients with failure after tendon to bone repair is relatively high. [34][35][36] The insertion of tendon/ ligament and bone is a strong mechanical structure established via a collagen fiber architecture and mineral composition in the native enthesis. 5,37-39 Therefore, it is likely that a fibrous membrane system that generates a fiber architecture and mineral composition will increase the feasibility of tendon to bone healing and may be the key to improve clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…If a standard primary arthroscopic exploration is performed, a subsequent decision to perform a secondary open treatment can be combined with the described approach. 1,16,17 As stated earlier, many techniques for the treatment of rotator cuff tears of the shoulder already have been described. Starting with Codman, followed by Bateman, De Palma, Neer, and other authors, 6 many variations of open surgery for rotator cuff tears have been described with increasing frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of arthroscopic cuff repair often highlight better visualisation, less deltoid damage, quicker postoperative recovery, better cosmesis and less risk of infection as possible advantages. A meta-analysis in 2016 of 18 studies on cuff repair, amongst them 4 randomised trials, concluded that there was no overall difference in outcome between mini-open and all-arthroscopic techniques 128 . The large UKUFF-study, published in 2017, with 273 randomised participants from 19 hospitals, did not show a clinically relevant difference between the two techniques in a 2-year follow-up 35 .…”
Section: Arthroscopic Cuff Repairmentioning
confidence: 99%